Factors That Guide the Diagnosis and Treatment Planning for Impacted Canines Using Three-Dimensional Cone-Beam Computed Tomography: A Cross-Sectional Study - Hasan Sabah Hasan; Mohamed A. Elkolaly; Ramy Elmoazen; Ayshan Kolemen; Arkan Muslim Al Azzawi (Hindawi Limited, 2022)
Objective. Impacted canines are one of the significant challenges in orthodontics that should be appropriately assessed to provide the best treatment to the patients. Materials and Methods. In the present study, 57800 patients were examined over six years to investigate the prevalence, diagnostic procedures, and treatment methodologies for impacted canine cases. Prevalence and diagnosis were tested using history taking, clinical examination, and three-dimensional cone-beam radiographs. The cases were tested for impaction site, gender, age, signs, and symptoms. The groups were classified for impaction location according to Mupparapu's classification. Result. The causative factors and the treatment methodology selected were plotted according to age and gender distribution. The total prevalence was 3.9% of canine impaction cases in relation to the total sample cases. The results showed a strong correlation between the site of impaction toward the upper arch and with distribution following Mupparapu's classification. The pain was the most detectable complication in all age groups, while root resorption was the least. Conclusion. Most of the younger age groups were sent for exposure and orthodontic traction, while the mid-aged groups elected for observation, and follow-up as their primary concern was esthetics. However, the adult patients were into exposure and traction to improve their function.